MOTIVASI BELAJAR BAHASA MANDARIN SISWA KELAS VIII SMP FRATER MAKASSAR - Reznun Mutmainnah; Misnawaty Usman; Burhanuddin Burhanuddin (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
REZNUN MUTMAINNAH, 2021. "Motivation to Learn Mandarin Students for Class VIII Students of Frater Makassar Junior High School". Thesis. Mandarin Education Study Program, Department of Foreign Languages, Faculty of Languages and Literature. Makassar State University (supervised by Misnawaty Usman and Burhanuddin).The method used in this study was quantitative descriptive that used questionnaires as a data collection technique. This study aims to determine what factors that influence that student’s motivation in learning Mandarin in SMP Frater Makassar grade VIII, the sample was taken from one class which consist of 33 students. The results showed that 51.5% of students practiced pronunciation in Mandarin, 63.6% of students were able to work on Chinese questions well, and 72.7% of students were motivated to learn Mandarin because of the teacher's role in providing direction during the learning process. included in the high category. Keywords : Motivation, Learning, Mandarin Languages.